The gonadotrophic response of Royal Marines during an operational deployment in Afghanistan. (23rd January 2015) - Hill, N. E.; Woods, D. R.; Delves, S. K.; Murphy, K. G.; Davison, A. S.; Brett, S. J.; Quinton, R.; Turner, S.; Stacey, M.; Allsopp, A. J.; Fallowfield, J. L.
Summary: Military training has been associated with changes in the hypothalamic–pituitary–gonadal axis consistent with central hypogonadism. Often such changes have been associated with body mass loss, though sleep deprivation and other psychological stress may also contribute. The effects of deployment in a combat zone on the hypothalamic–pituitary–gonadal axis in military personnel are not known. The objective was to investigate the hypothalamic–pituitary–gonadal axis in male military personnel deployed in Afghanistan. Eighty‐nine Royal Marines were investigated pre‐deployment, following 3 months in Afghanistan and following 2 weeks mid‐tour leave. Testosterone, sex hormone‐binding globulin (SHBG), follicle‐stimulating hormone (FSH), luteinising hormone (LH), 17‐hydroxyprogesterone, androstenedione (AD) and insulin were assayed and body mass recorded. The results showed that body mass (kg) dropped from 83.2 ± 9.2 to 79.2 ± 8.2 kg during the first 3 months of deployment ( p < 0.001). Total testosterone did not change, but SHBG increased (30.7 ± 9.7 vs. 42.3 ± 14.1 nmol/L, p < 0.001), resulting in a significant ( p < 0.001) fall in calculated free testosterone (435.2 ± 138 vs. 375.1 ± 98 pmol/L). Luteinising hormone and FSH increased by 14.3% ( p < 0.001) and 4.9% ( p = 0.003) respectively. Free testosterone, SHBG, LH and FSH returned to baseline following 2 weeks of mid‐tour leave. Androstenedione (AD) decreased by 14.5% ( p = 0.024), and insulin decreased by 26% ( p = 0.039), over the course of deployment. In this study of lean Royal Marines, free testosterone decreased during operational deployment to Afghanistan. There was no evidence to suggest major stress‐induced central hypogonadism. We postulate that reduced body mass, accompanied by a decrease in insulin and AD synthesis, may have contributed to an elevated SHBG, leading to a decrease in free testosterone.